PENDAMPINGAN KEGIATAN PENGENALAN LINGKUNGAN PRA- SEKOLAH BAGI MAHASISWA TINGKAT AKHIR DI MA PLUS NURUL ISLAM SEKARBELA - Dedi Riyan Rizaldi; Siti Rabiatul Fajri; Muhamad Zaenudin; Ziadatul Fatimah (LPPM Universitas Bina Bangsa, 2022)
Schools become the real and best environment for students as prospective teachers to gain various experiences. This condition is to maximize and test various learning theories that exist during college at university. The purpose of this activity is to assist final year students from the Mandalika Mataram University of Education in participating in the Preschool Environmental Introduction program at MA Plus Nurul Islam Sekarbela. Mentoring activities are carried out through three stages, including preparation, implementation, and evaluation. This activity was attended by 8 students who are currently in their final semester. The results of this activity show that the mentoring process really helps students in getting to know various things related to the school environment. In addition to students, this activity also provides more experience for accompanying teachers to be able to transfer knowledge and experience that they have previously had to students as future teacher candidates